We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
43
2
avatar

Suppose 1/x = 2/(y + z) = 3/(z + x) = (x^2 - y - z)/(x + y + z).  What is (z - y)/x?

 Nov 21, 2019
 #1
avatar+105370 
+1

Suppose 1/x = 2/(y + z) = 3/(z + x) = (x^2 - y - z)/(x + y + z).  What is (z - y)/x?

 

Using the first two equalities  we have that

 

(y  + z)  =  2x       (1)

 

And using the second two equalities we have that

 

2(z + x)  = 3(y + z)  ⇒  2(z + x)  =  3(2x) ⇒   2z = 4x   ⇒  z = 2x   (2)

 

Sub (1) into the last expression in the equality :

 

(x^2 - (y + z) )                 x^2 - 2x        x ( x - 2)          x - 2

____________  =        ________   =  _______  =    ____

(x + y + z )                       x + 2x            3x                   3

 

So  using this and the first expression we have that

 

x - 2               1

____  =       ____      cross-multiply

   3                 x

 

x^2 - 2x = 3

 

x^2 - 2x - 3  =  0     factor

 

(x - 3) ( x + 1)  =   0

 

So either x = 3   or    x  = -1

 

Which means that   z = 6    or  z  = -2

 

Let x  = -1    and z =  -2

 

(y + z) = 2x

( y - 2)  = -2

Which means that y  = 0

 

Note that....when x = -1 , z =  -2    we have that

 

1/x = 2/(y + z) = 3/(z + x) = (x^2 - y - z)/(x + y + z)

 

1/ -1  = 2 / (0 - 2)   =  3 / (-2 - 1)   =  [ (-1)^2 - 0 + 2 ] / [ -1 - 0 - 2]  =  

 

1/-1   =  2/-2  = 3/ -3  =  3/-3

 

-1  = - 1  = - 1  = - 1

 

So

 

(z - y )  / x   =

 

(-2 - 0) / -1   =

 

2

 

BTW......The same result would be found when x = 3  and z  = 6

 

cool cool cool

 Nov 21, 2019
edited by CPhill  Nov 21, 2019
edited by CPhill  Nov 21, 2019
edited by CPhill  Nov 21, 2019
 #2
avatar+23542 
+2

Suppose \(\dfrac{1}{x} = \dfrac{2}{y + z} = \dfrac{3}{ z + x} = \dfrac{x^2 - y - z}{x + y + z}\).  


What is \(\dfrac{z - y}{x}\) ?

 

\(\begin{array}{|rcll|} \hline \mathbf{\dfrac{1}{x}} &=& \mathbf{\dfrac{3}{ z + x}} \\\\ z + x &=& 3x \\\\ \mathbf{z} &=& \mathbf{2x} \\ \hline \end{array}\)

 

\(\begin{array}{|rcll|} \hline \mathbf{\dfrac{1}{x}} &=& \mathbf{\dfrac{2}{y + z}} \\\\ y+z &=& 2x \quad | \quad \mathbf{z=2x} \\\\ y+2x &=& 2x \\\\ \mathbf{y} &=& \mathbf{0} \\ \hline \end{array}\)

 

\(\begin{array}{|rcll|} \hline && \mathbf{\dfrac{z - y}{x}} \quad | \quad \mathbf{y=0} \\\\ &=& \dfrac{z}{x} \quad | \quad \mathbf{z=2x} \\\\ &=& \dfrac{2x}{x} \\\\ &=& \mathbf{2} \\ \hline \end{array}\)

 

laugh

 Nov 22, 2019

21 Online Users

avatar
avatar